Solar bubble dryer: alternative to sun drying for reducing drying losses in Bangladesh (Bangladesh Journal of Agriculture, 2022)
The Solar Bubble Dryer (SBD) is a latest low cost drying technology and flexible alternative to sun drying. Technical performance was investigated by observing moisture content and temperature distribution at different points of the dryer. The moisture distribution was uniform and its content was reduced initially from 19.5, 20.6 and 20.3% to 14, 15.6 and 14%, respectively in the 1st, 2nd and 3rd trial of the dryer. The temperature distribution was almost same but it was sometimes lower than the ambient temperature. The drying rate, drying capacity and drying efficiency were found to be 3.9 kg/hr, 1000 kg/batch, and 12.3%, respectively. Every trial took 3 - 5 days but it was difficult to achieve desired moisture of 12.0%. The average germination rate of SBD dried paddy (89.66%) was more than that of sun-dried paddy (84%). The milling recovery was found 71% for SBD dried paddy and 72.4% for sundried paddy. The percentage of broken rice in SBD dried paddy sample was more than that of sun-dried sample because of high moisture content (14.5%) and less hardness (22.5 N). The operating cost of paddy drying in SBD dryer was found Tk. 1410.9 per ton whereas that of traditional sun drying methods was found Tk.1047.3 per ton. Although, drying by SDB is not profitable over traditional drying, it has advantage to protect drying loss of fresh harvested paddy during unpredictable weather condition in rainy season.Bangladesh J. Agri. 2022, 47(1): 1-15